Frequency of Radix Entomolaris / Paramolaris in Permanent Mandibular First Molars of Patients Visiting Hamdard University Dental Hospital - Ali, Syed Abrar; Hussain, Mehmood; Shahzad, Muhammad; Tariq, Ahmed (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To see the prevalence of an additional root in permanent mandibular first molars in patients presenting for dental checkup for root canal treatment. METHODOLOGY: This observational study was carried out at Department of Endodontics, Hamdard University Dental Hospital, Karachi from June 2016 to May 2017. Sample size was Eight hundred and three permanent mandibular first molars from 568 females and 235 males were examined over a period of 1 year. Presence of a third root was revealed by diagnostic periapical radiographs and the comparison between males and females and between the right and left sides of the mandible were recorded. RESULTS: Out of the 803 permanent mandibular first molars that were observed, only 17 were found to have an accessory root. Out of total 803 samples that were being evaluated, only 17 subjects were found to have an extra root with a prevalence of 2.12%. The incidence of extra root was found to be higher in males. CONCLUSION: Though the incidence of radix entomolaris & paramolaris observed among the examined population was quite low, detection of radix is crucial to a successful endodontic treatment. More in depth study and detection methods are required for better identification of this unique anomaly.